THE PRECONDITIONS FOR THE FORMATION AND DEVELOPMENT OF THE NATIONAL QUALITY ASSURANCE FRAMEWORK IN HIGHER EDUCATION OF THE RA (Education in the 21st Century, 2023)
The article presents the dynamics of the formation and development of the National Quality Assurance Framework of the RA and also clarifies the achievements, issues and challenges in the field of quality assurance in the context of the EHEA. According to the results of this research, Armenia has made great efforts to apply the European approach to quality assurance. At the same time, it should be noted that the issues in the quality assurance system of higher education are largely conditioned by the problems of legislative regulations of education, non-revision of licensing and quality assurance criteria as well as non-reflection of the current developments of the EHEA reforms in the QA processes. Thus, more comprehensive measures are needed to make quality assurance processes targeted and reflect current trends in them. The result of the research also depicts that though the European and Armenian frameworks have similar goals and have passed a rather long period of development, for the successful implementation of the priorities of higher education sector of the RA, it is suggested to review the Armenian higher education strategy, standards and criteria, procedures and methodology and to target the whole efforts towards improving the quality of educational services, making the higher education of the RA more competitive and attractive in Armenia and in the EHEA.
Keywords: European Higher Education Area (EHEA), higher education quality assurance, QA sectorial issues, European Quality Assurance Framework, National Quality Assurance Framework of the RA.